The resilience of Jewish communities living in the diaspora: a scoping review - Meijer, Judith E. M.; Machielse, Anja; Smid, Geert E.; Schats, Winnie; Jong, Miek C. (Frontiers in Psychology, 2023)
Throughout history, Jewish communities have been exposed to collectively experienced traumatic events. Little is known about the role that the community plays in the impact of these traumatic events on Jewish diaspora people. This scoping review aims to map the concepts of the resilience of Jewish communities in the diaspora and to identify factors that influence this resilience. We followed the Joanna Briggs Institute (JBI) methodology. Database searches yielded 2564 articles. Sixteen met all inclusion criteria. The analysis was guided by eight review questions. Community resilience of the Jewish diaspora was often described in terms of coping with disaster and struggling with acculturation. A clear definition of community resilience of the Jewish diaspora was lacking. Social and religious factors, strong organizations, education, and communication increased community resilience. Barriers to the resilience of Jewish communities in the diaspora included the interaction with the hosting country and other communities, characteristics of the community itself, and psychological and cultural issues. Key gaps in the literature included the absence of quantitative measures of community resilience and the lack of descriptions of how community resilience affects individuals' health-related quality of life. Future studies on the interaction between community resilience and health-related individual resilience are warranted.